2018
DOI: 10.3390/medicina54040058
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Atrial Electromechanical Delay to Predict Atrial Fibrillation in Hemodialysis Patients

Abstract: Background and objective: Prevalence of atrial fibrillation is higher in hemodialysis patients as compared to the general population. Atrial electromechanical delay is known as a significant predictor of atrial fibrillation. In this study, we aimed to reveal the relationship between atrial electromechanical delay and attacks of atrial fibrillation. Materials and methods: The study included 77 hemodialysis patients over 18 years of age giving written consent to participate in the study. The patients were divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
2
7
1
Order By: Relevance
“…This electrical remodeling might be the etiology of AF. 30 QRS duration was an independent predictor of NOAF in this study, which was in concordance with previous findings. 31,32 The right and left atrium are composed of overlapping myocytes in the form of myocardial fibers that come together and create the atrial walls.…”
Section: Commentssupporting
confidence: 94%
“…This electrical remodeling might be the etiology of AF. 30 QRS duration was an independent predictor of NOAF in this study, which was in concordance with previous findings. 31,32 The right and left atrium are composed of overlapping myocytes in the form of myocardial fibers that come together and create the atrial walls.…”
Section: Commentssupporting
confidence: 94%
“…EMD is one of them and is defined as the time between the occurrence of force in the myocardium and the onset of electrical activity. The EMD, which is easily obtainable by tissue Doppler imaging (TDI), also indicates atrial conduction heterogeneity [20]. It is well known that increased atrial EMD in TDI is an indicator of supra-ventricular tachycardia development [21].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that atrial electromechanical delay predicts arrhythmias in studies conducted with adults and children. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Although its mechanism has not been completely understood in obesity, pro-inflammatory cytokines like interleukin-1, interleukin-6 and tumour necrosis factor-α which are secreted from visceral and epicardial adipose tissue may cause atrial electromechanical delay by causing inflammation in atrial tissue. 29 A decrease in visceral and epicardial adipose tissue may also cause a decrease in electromechanical delay by further reducing existing inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between PA septum and PA tricuspid (PA septum − PA tricuspid) was identified as an intra-atrial electromechanical delay, while the difference between PA lateral and PA tricuspid (PA lateral − PA tricuspid) was identified as an inter-atrial electromechanical delay. 17…”
Section: Tissue Doppler Echocardiographymentioning
confidence: 99%